Récit de guerre et éthique. Singularité, communauté et temporalité Adieu à tout cela de Robert Graves et La main coupée de Blaise Cendrars - Anne MOUNIC (E-REA)
After briefly recalling a few narratives written during or after the Great War and classifying them along two lines – either an idealistic view of death or the expression of the choice of life, ecstasy or a taste for everyday life, impersonal or personal standpoint, individualism and the individual voice – so as to highlight opposite views, I intend to compare two significant novels, written by volunteers, Goodbye to Al That / Adieu à tout cela? (1929) by Robert Graves (1895-1985) and La main coupée (1946) by Blaise Cendrars (1887-1961). Although both authors are different individuals, they have in common similar behaviours and thoughts. Both were wounded – Cendrars lost his right hand, the writer’s hand – and felt that their war experience was initiation to them and led them to their individual assertion among the others. Both of them considered it was their poetic duty to remember and sing their dead comrades. They both understood the ethical issue raised by the war, which Graves called “murder” until the very end of his life. Cendrars wrote an essay called “J’ai tué”.The war experience caused those two poets to refuse the idealistic dualism of the absolute; they rejected the post-war exaltation of manhood, as described by G.L. Mosse, and never indulged in an aesthetic view of war in the perspective of Ernst Jünger or Louis-Ferdinand Céline, to mention only those authors. Considering the war narratives along those lines induces an interesting reflection which may help us to understand even the present moment.